2019
DOI: 10.1029/2018jc014444
|View full text |Cite
|
Sign up to set email alerts
|

Observation and Parameterization of Broadband Sea Surface Albedo

Abstract: The broadband sea surface albedo (SSA) was observed from a fixed sea platform in the South China Sea. This observation period lasted approximately 152 days and included a wide range of atmospheric and oceanic conditions. Under clear‐sky conditions, the observed SSA increased significantly with the increase in the solar zenith angle at low solar altitudes, while the SSA changed little under high Sun. Under cloudy skies, however, the SSA was negligibly dependent on the solar zenith angle. The observed SSA was al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…The sea surface albedo is another key parameter in climate systems. Based on about 5 months of in-situ observations, Huang et al (2019) found that albedo increases with the increase of winds or surface waves and decreased with increasing water vapor pressure at the sea surface, which is a process by means of which surface waves impact on air-sea heat fluxes. Li et al (2021) demonstrated another important wave-coupled mechanisms, this time in polar regions.…”
Section: Air-sea Heat Fluxmentioning
confidence: 99%
See 1 more Smart Citation
“…The sea surface albedo is another key parameter in climate systems. Based on about 5 months of in-situ observations, Huang et al (2019) found that albedo increases with the increase of winds or surface waves and decreased with increasing water vapor pressure at the sea surface, which is a process by means of which surface waves impact on air-sea heat fluxes. Li et al (2021) demonstrated another important wave-coupled mechanisms, this time in polar regions.…”
Section: Air-sea Heat Fluxmentioning
confidence: 99%
“…Based on about 5 months of in‐situ observations, Huang et al. (2019) found that albedo increases with the increase of winds or surface waves and decreased with increasing water vapor pressure at the sea surface, which is a process by means of which surface waves impact on air‐sea heat fluxes. Li et al.…”
Section: Air‐sea Heat Fluxmentioning
confidence: 99%
“…This behavior is caused by the transition from a completely and continuously glaciated northern ocean, and a mostly open ocean. Oceans have a very low albedo even compared to Martian regolith (∼0.05 6 versus 0.215; see, e.g., Huang et al 2019, for data on the former), thus they contribute to warm up the planet. Since the ocean fraction is highest in the C0GN model, their effect is strongest.…”
Section: Dependence On Obliquitymentioning
confidence: 99%
“…The surface reflectivity of the oceans is modelled using empirical laws that take into account its dependence on 𝑍 and the fact that the water surface is not smooth. We compared previous algorithms published in the literature (Briegleb et al 1986;Enomoto 2007) with a recent set of measurements obtained at different values of 𝑍 (Huang et al 2019). The observational data (red dots in Fig.…”
Section: Ocean Albedomentioning
confidence: 99%